Pengaruh pengukuran sifat fisis dan sifat mekanis papan partikel sampah daun kering berdasarkan ukuran butir (The effect of measuring the physical properties and mechanical properties of the dry leaf waste particleboard based on grain size) - Ade Usra Berli; Yenni Darvina; - Yulkifli (Department of Physics – Universitas Negeri Padang UNP, 2013)
ABSTRACT Utilization of leaf waste processed a drop of without development in the processing. The thought of leaf waste can be processed to become products of economic value, one used as raw material similar lightweight particle board, particle board can be used as a substitute for wood. Particle board manufacturing is done by printing the leaf waste that has been mixed with a binder or adhesive. Adhesives used as binder is polyvinyl acetate (PVAC). Leaf waste material made with a variety of different grain sizes are 1.7 mm, 2.8 mm and 4.75 mm. Particle board manufacturing process is done by inserting the material into the machine hot press with pressure 330 x 104 kg/m2 at 100 ° C for 20 min. From the testing of physical and mechanical properties, obtained the following results: for the physical properties of particle board dry leaf waste, the small grain size of particle board then dried leaf waste moisture content decreases while the value of the density and thickness development is increasing. For the mechanical properties of particle board, the small grain size of particle board then the value of flexural strength and compressive strength increased. Test results obtained water content and density to meet the Standar Nasional Indonesia (SNI 03-2105-2006), while the value of developing strong and thick flexible does not meet the Indonesian National Standard (SNI 03-2105-2006). For compressive strength values no set of Standar Nasional Indonesia. Grain size optimal particle board in this study is the size of a small grain size of 1.70 mm. Keywords: Leaf of Mangoes, polyvinyl acetate (PVAc), Particle board